Pengaruh Kompetensi SDM, Sistem Pengendalian Internal Pemerintah, dan Whistleblowing System Terhadap Pencegahan Fraud Dalam Pengelolaan Dana BOSP - Setiawan, Rian Adi; Sari, Fangela myas (Journal of Management and Economics Innovation, 2025)
The purpose of this study is to analyze the influence of human resource competencies, government internal control systems, and whistleblowing systems on fraud prevention. The sample used in this study consisted of 72 respondents who were educators and educational staff at public elementary schools in the South Pekalongan District. This study used a simple random sampling method..  This research uses a quantitative approach with descriptive analysis, and the data collection technique is in the form of questionnaire questions. The data used in this research is primary data. Primary data is in the form of responses from respondents via questionnaires. The data analysis used is multiple linear regression analysis. The results of this study indicate that human resource competencies, government internal control systems, and whistleblowing systems have a significant effect on fraud prevention and financial reporting. This study concludes that human resource competencies, government internal control systems, and whistleblowing systems have a significant effect on fraud prevention, which ultimately affects the quality of financial reports.